Prospects for probiotics use as the gut microbiota modulators in obesity (literature review) - D.K. Miloslavsky; S.M. Koval (Mìžnarodnij Endokrinologìčnij Žurnal, 2022)
The review of foreign sources of literature from the PubMed scientometric database examines the issue of prospects for the use and effectiveness of probiotics as modulators of gut microbiota in obesity. The authors provide data on the pathogenetic role of gut microbiota and its derivatives, first of all short-chain fatty acids, in metabolically associated diseases, such as obesity. We provide a historical reference, the classification of this group of biologically active drugs, list of guidelines on their use, the leading mechanisms of action of probiotics, primarily in obesity, their favorable effects on anthropometric indicators, parameters of lipid-carbohydrate homeostasis, the leading biomarkers associated with disease. Data are given on the prospects for prescribing probiotics in morbidly obese people after bariatric surgery; the attention is focused on food products with probiotic properties; the issue of further research and the safety of using probiotic drugs is considered, taking into account a number of requirements for their effective use. Probiotic preparations may have a beneficial effect as a complementary therapy to fight obesity when used for a long time in high doses. Several experimental and clinical studies reported a decrease in body weight, the levels of glucose, lipid and other biomarkers when taking probiotics. Short-term (≤ 12 weeks) use of probiotics contributed to a decrease in body mass index and body fat percentage, but the intensity of these effects was small. Gut microbiota modulation using multistrain probiotics may be a valuable tool in addition to traditional lipid-lowering agents and anorexigens. In conditions of growing interest in the methods of microbiological therapy, the active use of drugs of this group, probiotic market saturation, the question of the safety of probiotic strains is of particular importance.